The Persian Companion Dirar Ibn Al-Azwar, his life and the rest of his poetry (Journal of the College of Basic Education, 2022)
The greatness of our heritage was evident from pre-Islamic and Islamic poetry, being an important part of civilization and testifying to the originality of our past.